Studying the efect of nanoliquids on the operational properties of brick building structures - Kropyvnytska, Tetiana; Semeniv, Roksolana; Kotiv, Roman; Kaminskyy, Andriy; Hots, Vladyslav (Eastern-European Journal of Enterprise Technologies, 2018)
The study reported here has established that the ceramic facing brick is characterized by capillary porosity that increases indicators of water absorption and capillary pull, as well as efflorescence formation at its surface. In order to protect the surface of such a brick and to provide it with the improved performance properties, we have used hydrophobizing substances. We have determined experimentally that the application of the PMPhS- and AP-based hydrophobizing agents leads to a decrease in porosity by 1.2-1.3 times, in water absorption ‒ by 1.2‒2.3 times, in water absorption at capillary pull ‒ by 1.1‒3.2 times. Research into frost resistance has found that for the ceramic brick, covered with PMPhS, it increases by 15 cycles, and when treating a brick surface with AP ‒ by 20 cycles, compared to the untreated brick (F50). By employing an electron microscopy, it was determined that the alternating freeze-thawing leads to that the brick's surface, treated with PMPhS and AP, demonstrates the formation of microcracks (in this case, water absorption increased by 42 and 28 %). By applying a method of mathematical planning of the experiment, it was found that the most effective hydrophobizing substance is the modifier that contains the nano-Al2O3 powder (a nano-liquid). It was determined that when treating the surface with a nano-liquid (the amount of nanо-Al2O3 is 0.8 %), its water absorption decreases to 1.2‒1.6 %, its water absorption indicator at capillary pull ‒ to 0.08‒0.12 kg/m2∙h0.5. Using a method of defectoscopy, applying the Karsten tube, it was found that water absorption for the brick whose surface was coated with a nano-liquid reduced from 0.15 to 0.002 ml/cm2, indicating a high level of hydrophobization. The electron microscopy method confirmed that the modification of the ceramic brick surface by the hydrophobizing nano-fluids makes it possible to compact the structure through the colmatation of pores and microcracks, which reduces the capillary pull of the brickwork. That also leads to the improved atmospheric and frost resistance of brick building structures. Thus, there is a reason to argue about the possibility of improving the physical and technical indicators of the brick building structure by modifying the surface of the ceramic facing brick by a nano-fluid